Inhibition of amyloid formation of prion fragment (106–128) by polyphenolic compounds - Regmi, Deepika; Haque, Seymour; Karim, Md Raza Ul; Stanic, Aleksander; Du, Deguo (Biochimica et biophysica acta. General subjects, 2025)
Prion diseases are characterized by the self-association and amyloid formation of misfolded prion proteins. Developing effective inhibitors of protein aggregation is critical for therapeutic intervention. In this study, we systematically evaluated a range of polyphenolic compounds as potential inhibitors of amyloid fibril formation of PrP(106–128), a prion fragment crucially involved in prion aggregation and propagation. Our findings demonstrate that the basic aromatic backbone structure of flavone alone is insufficient to inhibit PrP(106–128) amyloid formation. Remarkably, flavone molecules containing adjacent hydroxyl groups on the phenolic B or A ring efficiently inhibited PrP(106–128) fibrillization, whereas compounds lacking vicinal hydroxyl groups were less effective in inhibiting amyloid formation. Epigallocatechin-3-gallate (EGCG) was one of the most potent inhibitors found in this study, with the gallate moiety playing an active role in the inhibitory function. Our findings indicate a structure-dependent inhibition activity of the phenolic small molecules, where the number and positioning of hydroxyl groups on the phenyl ring play a pivotal role in inhibiting the aggregation of the peptide. The auto-oxidation of the catechol or pyrogallol moieties to form quinone structures, followed by their reaction with amino acid side chains of the peptide to form covalent adducts, likely account for the inhibitory activity of these phenolic compounds on PrP(106–128) amyloidogenesis. These results will help the design of novel polyphenolic molecules with optimized structural features as potent inhibitors of amyloid formation of both PrP(106–128) and the full-length prion proteins. [Display omitted] •Basic aromatic backbone structure of flavone alone cannot inhibit PrP(106–128) amyloid formation.•Flavonoids containing adjacent hydroxyl groups on the benzene ring are efficient inhibitors.•Flavonoids without adjacent hydroxyl groups show much weaker inhibitory activity.•Auto-oxidation of catechol moieties and covalent linkage to PrP(106–128) may account for the strong inhibitory activity.